Metastable Helium Lidar for Thermosphere and Lower Exosphere Measurements: Instrument Description and Initial Results - Ruocan Zhao; Zhenwei Liu; Xianghui Xue; Hang Zhou; Zhaofeng Wang; Yingyu Liu; Jiangtao Li; Dongsong Sun; Jiaxin Lan; Tingdi Chen; Dongfeng Zhao; Xiankang Dou (Space Weather)
Abstract In this work, we present a metastable helium lidar system for the measurements of metastable helium He(23S) density in the thermosphere and lower exosphere. This lidar system consists of a high power 1,083 nm pulsed laser, a 1 m aperture laser beam expander, six 1 m aperture receiving telescopes and a superconducting nanowire single‐photon detector (SNSPD). This system realizes metastable helium density detection up to 1,000 km. Daily rapid variation of metastable helium density within several hours was measured with a height resolution of 50 km for the first time. It demonstrates the capability of ground‐based lidar for continuous height‐resolved detection of the atmospheric metastable helium in the height range of 200–1,000 km. This is a promising tool to help study the coupling of neutral and ionized atmosphere in this height range and further providing observation basis for space weather prediction.